2006
DOI: 10.1002/prep.200600025
|View full text |Cite
|
Sign up to set email alerts
|

Combustion of Environmentally Altered Molybdenum Trioxide Nanocomposites

Abstract: Nanocomposite thermite mixtures are currently under development for many primer applications due to their high energy densities, high ignition sensitivity, and low release of toxins into the environment. However, variability and inconsistencies in combustion performance have not been sufficiently investigated. Environmental interactions with the reactants are thought to be a contributing factor to these variabilities. Combustion velocity experiments were conducted on aluminum (Al) and molybdenum trioxide (MoO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…It also should be noted that the bonded water (or chemisorbed water) is actually separated from the Al particles because it is bonded to the WO 3 particles (and inherent in the WO 3 synthesis process). In contrast, humidity-induced Al oxidation (which is a relatively slow process and usually associated with the degradation of the Al combustion performance with aging) is a completely different phenomenon because the water molecules that are derived from environmental humidity are “attached” to the Al particles. In this way, the oxidation processes are different because, for humidity-induced oxidation, the water is directly diffusing into Al particles through the alumina shell, whereas the bonded water must first separate molecularly from their WO 3 host prior to diffusing toward the Al particles.…”
Section: Discussionmentioning
confidence: 99%
“…It also should be noted that the bonded water (or chemisorbed water) is actually separated from the Al particles because it is bonded to the WO 3 particles (and inherent in the WO 3 synthesis process). In contrast, humidity-induced Al oxidation (which is a relatively slow process and usually associated with the degradation of the Al combustion performance with aging) is a completely different phenomenon because the water molecules that are derived from environmental humidity are “attached” to the Al particles. In this way, the oxidation processes are different because, for humidity-induced oxidation, the water is directly diffusing into Al particles through the alumina shell, whereas the bonded water must first separate molecularly from their WO 3 host prior to diffusing toward the Al particles.…”
Section: Discussionmentioning
confidence: 99%
“…The easiest method is the physical powder mixing. In recent works, the ultrasonic mixing is mostly employed to combine nano-Al and oxidizer powder [40], [47]- [50], [54]- [56]. Typically, the nano-Al and oxidizer are dispersed in solvents (e.g., hexane) and mixed together with ultrasonic wave.…”
Section: A Powder Mixingmentioning
confidence: 99%
“…It was reported that after treating MoO 3 nanoparticles in 99% relative humidity atmosphere for 1 day, the Al/MoO 3 nanocomposite exhibited a reduction in burn velocity of over 99%. 41 The humidity of air differs according to locations and climates. Consequently, concerns arise in that while the freshly prepared nanocomposites are capable of superior properties, the performance can degrade significantly after long-distance transportation and/or long-term storage.…”
Section: Introductionmentioning
confidence: 99%
“…Some widely used oxidizers are hydrophilic (e.g., CuO) or even hygroscopic, which makes performance maintenance a big issue. It was reported that after treating MoO 3 nanoparticles in 99% relative humidity atmosphere for 1 day, the Al/MoO 3 nanocomposite exhibited a reduction in burn velocity of over 99% . The humidity of air differs according to locations and climates.…”
Section: Introductionmentioning
confidence: 99%